Family, self, and human development across cultures theory and applications - Kagitcibasi, Cigdem (Routledge, 2017)
Çiğdem Kağıtçıbaşı's influential volume was a work of masterful scholarship and field-defining thought that challenged the existing assumptions in mainstream western psychology about the nature of individuals. During the past two decades since its publication, cultural and cross-cultural research and theory on the self, family, and human development have expanded greatly, developing fruitfully from the basic issues and paradigms Kağıtçıbaşı explored. This Classic Edition provides a critical assessment, consideration, and reflection of recent scholarship in this field. It brings this essential work up to date and appraises it in the light of current prevailing perspectives.--Provided by publisher.